PENANAMAN PENGETAHUAN VERB DALAM BAHASA INGGRIS UNTUKPENGAJARAN WRITING - Setiarini, Riskia (Jurnal Pengembangan Pendidikan, 2012)
Abstract. Failure made by my students ofWriting 01 class in recognizing and using verbs in different functions equippedby their counterparts, that are auxiliaries, triggered me to compose particularmaterials of writing class: the basic level. This insight is mostly based onthe concept offered by Deterding and Poedjosoedarmo (2002) on verbs. This isthen supported by other concepts on verbs, combined together with my resume onhow to make ease studentsâ comprehension on verbs in relation to theimplementation of predicates,Â in termsof verbal and nominal sentences as the core. I argue that these sequence ofmaterials with emphasis on verbs are beneficial, in a way that these will breakdown studentâs failure on comprehending what parts of speech are, what verbs andtheir forms as well as their functions, how the verbs are applied in tenses,how to use other forms of verbs, i.e. have + past participle, to be + pastparticiple, and such. Yet, this insight is expected to contribute to theteaching learning activities, in particular, for the sake of implantingknowledge on verbs to students that help them in obtaining writing ability. Â Keywords: writing,verbs, predicate, auxiliaries, linking verbs